Pengaruh Dana Simpanan Wadiah Terhadap Bonus Wadiah Pada Bank Syariah Indonesia Periode 2021-2024 - Rahma Sari Zein; Srisudiarti; Anggraini, Tuti (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study was conducted to examine the effect of wadiah savings funds on wadiah bonuses at PT Bank Syariah Indonesia. Wadiah bonuses are an important issue in Islamic banking as they represent a form of reward given to customers for their deposits, which can influence customers' decisions in choosing Islamic banking products. In this context, a better understanding of the factors affecting wadiah bonuses is crucial to enhancing the appeal of Islamic banking products and retaining customers. The variable